The Effect of Inquiry-Based Learning on Developing Scientific Research Skills and Motivation in Science among Preparatory Stage Students in Public Schools – Northern District - Omari, Safa Ahmad Khaled Mareed; Aqel, Fawaz Muhmad Abed (Journal of Educational and Psychological Sciences, 2025)
The study aimed to investigate the effect of inquiry-based learning on developing scientific research skills and enhancing motivation among lower secondary school students in science. A purposive sample of 168 female students from Al-Zahraa Lower Secondary School “B” in Nazareth, affiliated with the Directorate of Public Education in the Northern District, was selected during the 2024/2025 academic year. Employing a quasi-experimental design, the study utilized a scientific research skills scale and a motivation scale for learning science. Results revealed statistically significant differences in scientific research skills in favor of the experimental group, as well as significant differences in motivation, indicating that inquiry-based teaching positively influenced students’ motivation in science. The study recommended expanding the application of inquiry-based learning strategies in teaching science and other subjects, and developing inquiry-based units tailored to learners’ cognitive levels and developmental stages.
Keywords: Inquiry-Based Learning; Scientific Research Skills; Motivation